Hiya al-Umm, Qaṣīdah Qālahā Zakir Shariff fī Rithā’ Ummihi: Dirāsah Taḥlīlīyah Adabīyah - Yunus, Idris Ahmad; Kabir, Saleh Muhammad; Gaji, Bashir Alhaji (Al-Ma‘rifah, 2021)
This study aims to study the life of Zakir Shariff and his elegy poem. The method used in this study is the descriptive-analytical approach, where the researchers read the selected poem and then follow it with study and analysis. The poem chosen was Hiya al-Umm, an elegy poem for his mother. The results of this study indicate that the beginning of the poem (maṭla‘ al-qaṣīdah) invites the reader to follow his elegy (rithā’) poem for his mother; (2) good disposal (ḥusn al-takhalluṣ) of the poem, the poet proceeded directly with the topic, noting that he did not explore the introduction of his poem with depict the remaining of the camps (al-ṭalalīyah) or propaganda; (3) a good syllable (ḥusn al-maqṭa‘) in the poem, the last words upon which the poet stood was well tolerated and kept a pleasure in listening in the most eloquent expression and the most beautiful meaning; (4) the sincerity of emotion (ṣidq al-‘āṭifah), the poem was distinguished by the sincerity of emotion, the heat of feeling, and the acuity of feeling.